Genetic Variation in Neisseria meningitidis Does Not Influence Disease Severity in Meningococcal Meningitis - Kremer, Philip H. C.; Lees, John A.; Ferwerda, Bart; van de Ende, Arie; Brouwer, Matthijs C.; Bentley, Stephen D.; van de Beek, Diederik (Frontiers in Medicine, 2020)
Neisseria meningitidis causes sepsis and meningitis in humans. It has been suggested that pathogen genetic variation determines variance in disease severity. Here we report results of a genome-wide association study of 486 N. meningitidis genomes from meningococcal meningitis patients and their association with disease severity. Of 369 meningococcal meningitis patients for whom clinical data was available, 44 (12%) had unfavorable outcome and 24 (7%) died. To increase power, thrombocyte count was used as proxy marker for disease severity. Bacterial genetic variants were called as k-mers, SNPs, insertions and deletions and clusters of orthologous genes (COGs). Population-level meningococcal genetic variation did not explain variance in disease severity (unfavorable outcome or thrombocyte count) in this cohort (h2 = 0.0%; 95% confidence interval: 0.0 – 0.9). Genetic variants in the bacterial uppS gene represented the top signal associated with thrombocyte count (p-value = 9.96e-07) but this did not reach statistical significance. We did not find an association between previously published variants in lpxL1, fHbp and tps genes and unfavorable outcome or thrombocyte count. A power analysis based on simulated phenotypes based on real genetic data from 880 N. meningitidis genomes showed that we would be able to detect a continuous phenotype with h2 >= 0.5 with the population size available in this study. This rules out a major contribution of pathogen genetic variation to disease severity in meningococcal meningitis, and shows that much larger sample sizes are required to find specific low-effect genetic variants modulating disease outcome in meningococcal meningitis.